The Effect of Using Picture Series toward Students’ Speaking Skill at the Second Grade in MTSS Nagari Binjai - Chairani Annisa; Reflinda Reflinda; Melyan Melani; Veni Roza (Universitas Maritim AMNI Semarang, 2022)
The purpose of this research was to determine the effect of using picture series on students' speaking skill. The researcher had done at MTSS Nagari Binjai. The problems in this research was caused by several factors. Firstly, students paid less attention to the English teacher. Secondly, they were afraid of making mistake to express ideas. In this research a quasi-experimental design was used by the researcher. The researcher used pre-test and post-test to experimental and control class. The sample was 2A as experimental class and taught by using picture series and 2B as control class and taught without using picture series. To determine the sample, the experimental and control class, the researcher utilized SPSS 20 to examine the data and check for normality and homogeneity. The researcher utilized the t-test formula to test the hypothesis and consulted the results in a t-table with level of significance of 0.05. It was found that there was a significant effect of using picture series toward students speaking skill. Then there was a significant difference between students who were taught using picture series and those who were taught without them. The value of t-calculated in the post-test from the experimental and control classes was greater than the t-table (3.4 > 2.021). The last hypothesis was that teaching with picture series was superior than teaching without picture series in terms of improving students' speaking skill. In the post-test, the mean score of the experimental class was greater than the control class (8.10 > 2.54).